What monetary incentives are rice farmers willing to accept to stop straw burning? Evidence from a choice experiment in the Mekong Delta, Vietnam - Cuong, Ong Quoc; Demont, Matty; Pabuayon, Isabelita M.; Depositario, Dinah Pura T. (Elsevier, 2024)
Producing rice generates straw, which is often conveniently burned, causing substantial atmospheric pollution. Increasing straw utilization efficiency and reducing straw burning will improve the agricultural ecological environment and promote sustainable development of agricultural production. Little is known about farmers’ perceived costs of alternative straw management practices and what it would take for them to stop straw burning. We conduct choice experiments with 543 Vietnamese farmers in the Mekong Delta to elicit their preferences for improved straw management practices under varying monetary incentives and enabling environments of mechanization and governance. The attributes and levels used in this study include sustainable practice (i.e., incorporation of rice straw, partial removal, and complete removal), availability of machinery (i.e., low, medium, and high), governance (i.e., individual farmer, farmer organization, and local government), and monetary incentives (US$43–87/ha). Results from a mixed logit model suggest that farmers are willing to stop straw burning and adopt sustainable straw management practices in return for monetary incentives. Farmers require lower monetary incentives when machinery services for chopping and collecting rice straw are available and when rice straw management is governed collectively by farmer organizations or the local government. Policy makers can use these results to prioritize investments and design optimal policies for mitigating air pollution by diverting farmers away from straw burning towards sustainable rice straw management practices.